2000
DOI: 10.1152/ajplung.2000.279.1.l25
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of alveolar monocyte recruitment in acute respiratory distress syndrome

Abstract: In 49 acute respiratory distress syndrome (ARDS) patients, the phenotype of alveolar macrophages (AMs) was analyzed by flow cytometry. Bronchoalveolar lavage (BAL) was performed within 24 h after intubation and on days 3-5, 9-12, and 18-21 of mechanical ventilation. The 27E10(high)/CD11b(high)/CD71(low)/ 25F9(low)/HLA DR(low)/RM3/1(low) AM population in the first BAL indicated extensive monocyte influx into the alveolar compartment. There was no evidence of increased local AM proliferation as assessed by nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
134
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(144 citation statements)
references
References 47 publications
9
134
0
1
Order By: Relevance
“…Recent observations from our group demonstrated that highly elevated CCL2 levels in BAL fluids of critically ill patients with septic ARDS were associated with the severity of respiratory failure (15). Because septic ARDS patients are at considerably increased risk of developing fibrotic responses in the late phase of the disease, it will be important to evaluate whether CCL2-triggered mechanisms outlined in the current study may also apply to patients with septic ARDS, where increased CCL2 levels and sustained inflammatory activation coincide within the same lung compartment.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recent observations from our group demonstrated that highly elevated CCL2 levels in BAL fluids of critically ill patients with septic ARDS were associated with the severity of respiratory failure (15). Because septic ARDS patients are at considerably increased risk of developing fibrotic responses in the late phase of the disease, it will be important to evaluate whether CCL2-triggered mechanisms outlined in the current study may also apply to patients with septic ARDS, where increased CCL2 levels and sustained inflammatory activation coincide within the same lung compartment.…”
Section: Discussionmentioning
confidence: 92%
“…Fibroproliferative responses are clinical complications frequently developing in the late phase of acute lung injury, as observed in severe pneumonia leading to acute respiratory distress syndrome (ARDS) (13)(14)(15). Examination of lung tissue sections from S. pneumoniae-infected mice of the two treatment groups revealed that 75% of the CCL2 overexpressing mice as compared with 25% of the wild-type mice developed bronchiolitis obliterans with organizing pneumonia by day 7 postinfection (Fig.…”
Section: Ccl2 Overexpressing Mice Respond To Challenge With S Pneumomentioning
confidence: 98%
“…PBMs are increasingly being recognized in many organ systems as orchestrators of leukocyte recruitment (11,22), prime initiators of endothelial damage (44,45), and pivotal contributors to fibrogenesis (32,46). However, despite the significant body of work suggesting that monocytes contribute to ALI (11,13,16,39,44,45,(47)(48)(49), no published reports exist of therapeutic monocyte depletion in established experimental ALI. We hypothesized in this study that infiltrating PBMs play a major role in regulating ongoing neutrophil recruitment and consequent vascular leak and that depletion of the PBM pool is a therapeutic target in the setting of established ALI.…”
Section: Discussionmentioning
confidence: 99%
“…These descriptions, alongside the recent discovery of patrolling sentinel monocytes within the vasculature (6), highlight PBMs' potential role in sensing and directing the inflammatory response. The importance of PBMs in acute inflammation offers a potential therapeutic window because they mobilize from the bone marrow and circulate in the peripheral vasculature before tissue infiltration in ALI (14)(15)(16). Hence, targeting PBMs and the mechanisms by which they could influence neutrophil emigration may provide a valuable interventional strategy.…”
mentioning
confidence: 99%
“…Macrophages are polarized by environmental cues and adopt different phenotypes. M1 proinflammatory and M2 antiinflammatory phenotypes are associated with the acute and resolving phases, respectively, of inflammation in ARDS (4,5). Mesenchymal stromal cells (MSCs) are increasingly recognized as a promising candidate therapy for ARDS (6).…”
mentioning
confidence: 99%